2014
DOI: 10.4067/s0034-98872014000200016
|View full text |Cite
|
Sign up to set email alerts
|

Massive and painful ascites as a presenting manifestation of systemic lupus erythematosus flare: a case report and literature review

Abstract: Lupus peritonitis (LP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Serositis is one of the major organ involvements and observed in 10%-30% of lupus patients (Man and Mok 2005;Al Arfaj and Khalil 2009). Pleural and pericardial involvements are common; however, peritoneal serositis, which is also called lupus peritonitis, is rare (Man and Mok 2005;Prasad et al 2012;Zhou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Serositis is one of the major organ involvements and observed in 10%-30% of lupus patients (Man and Mok 2005;Al Arfaj and Khalil 2009). Pleural and pericardial involvements are common; however, peritoneal serositis, which is also called lupus peritonitis, is rare (Man and Mok 2005;Prasad et al 2012;Zhou et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Serositis is commonly seen in patients with connective tissue disease (CTD) such as systemic lupus erythematosus (SLE), where there is no macroscopic lesion in the peritoneal cavity. Lei Zhou et al reported a patient who had massive and painful ascites as a prominent manifestation of SLE, in the absence of other well-recognized clinical features of SLE and the common causes of ascites [ 12 ]. Crohn's disease is a granulomatous inflammatory bowel disease which presents differently according to the lesion location, type, and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic, multi-organ autoimmune disease. It frequently involves the gastrointestinal system and serosal tissues [ 1 ], while peritoneal involvement is very rarely described [ 2 ]. The symptoms of SLE are usually vague and non-specific, contributing to the challenge of diagnosing it in the emergency department (ED).…”
Section: Introductionmentioning
confidence: 99%